The Role of Art Elements in the Translation of Photographic Works - Azman, Mohammad Firdaus (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018)DO - 10.24191/idealogy.v3i2.70, 2018)
The presence of photography around the 1890s when Malaya (now Malaysia) which was still under British rule was not an obstacle for the field of photography to grow to this day. Photography is a medium that can be used to produce creative works that have their own artistic elements (Sabki Md. Noh, M. Shariful Hafizal, 2017). The production of the work is produced according to technical procedures that require repeated experimentation to get the best results. Emphasizing the element or line element in the production of a work is none other than to show the relevance of the art element in photography, but also to focus on the use of pattern elements. In the form of social relationships, the artist tries to convey that when filming, visuals should always be taken with care so that every art element that is blended in the production of the work is not overwhelmed or runs away from the original concept. For the artist, this visual is a conversation about what is done as well as what can be conveyed, in addition to aiming to make the audience aware of the artist’s creative process while creating, which illustrates the meaning of the artist’s work which usually describes literary language in visual form. With the role of photography that also gives awareness of the importance of understanding the adaptation of visual art elements Keywords: Photography, artistic elements, art work, consciousness Keywords: Photography, art element, art, realization